2016
DOI: 10.1080/10256016.2016.1141205
|View full text |Cite
|
Sign up to set email alerts
|

Online induction heating for determination of isotope composition of woody stem water with laser spectrometry: a methods assessment

Abstract: Application of stable isotopes of water to studies of plant-soil interactions often requires a substantial preparatory step of extracting water from samples without fractionating isotopes. Online heating is an emerging approach for this need, but is relatively untested and major questions of how to best deliver standards and assess interference by organics have not been evaluated. We examined these issues in our application of measuring woody stem xylem of sagebrush using a Picarro laser spectrometer with onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…All three CRDS methods performed satisfactorily for the pure water check standards, as expected from previous measurements with the L2120‐ i with vaporizer, the L2120‐ i with MCM, the L2120‐ i with an IM, and the L2130‐ i with an MCM . For the soil distillates, the L2120‐ i with vaporizer and the L2130‐ i with an IM produced consistent results with relatively minor errors that were within the lower end of the range of errors previously reported for soil distillates .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…All three CRDS methods performed satisfactorily for the pure water check standards, as expected from previous measurements with the L2120‐ i with vaporizer, the L2120‐ i with MCM, the L2120‐ i with an IM, and the L2130‐ i with an MCM . For the soil distillates, the L2120‐ i with vaporizer and the L2130‐ i with an IM produced consistent results with relatively minor errors that were within the lower end of the range of errors previously reported for soil distillates .…”
Section: Discussionsupporting
confidence: 83%
“…The third study examined the performance of the full IM system (including the MCM) for stem samples, and found that this configuration produced substantial errors relative to CVD and IRMS . The basis of the errors was not clear in this third study because the IM extractions appeared to be complete and there did not appear to be evidence of spectral interference from co‐extracted organic compounds …”
Section: Parameters Used To Diagnose Spectral Interference the Raw Vmentioning
confidence: 95%
See 1 more Smart Citation
“…First, a number of other types of interference have been studied in the L2120-i. Previous work has characterized interference from self-broadening (Schmidt et al, 2010) and from organic contaminants (Brand et al, 2009;West et al, 2010), tested algorithms for correcting for organic interference during or after analysis (Hendry et al, 2011;Schultz et al, 2011;West et al, 2011;Schmidt et al, 2012;Martín-Gómez et al, 2015;, and tested peripherals for pyrolyzing or oxidizing organic contaminants prior to analysis (Berkelhammer et al, 2013;Martín-Gómez et al, 2015;Lazarus et al, 2016). Second, the L2120-i has been widely used to measure δ 18 O-H 2 O and δ 2 H-H 2 O values in situations where background variation could be relevant to the calibration procedures and/or the fundamental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…IM-CRDS produces accurate δ 2 H and δ 18 O data (i.e., comparable with IRMS measurements) when leaf, stem or soil samples are extracted via CVD and the liquid water is then applied to glass filters and measured by IM-CRDS, 5,7 although correction for spectral interference from organic contaminants is needed in some cases. 5 However, for solid leaf, stem, or soil samples that are directly extracted on the IM, even with correction for organic contamination, the differences between the IM-CRDS and CVD-IRMS values (as high as 10‰ for δ 18 O values and 50‰ for δ 2 H values) 5,7 can be of the same order of magnitude as the differences between signals of interest in natural abundance studies (e.g., δ 2 H difference of~35‰ in xylem water of streamside vs non-streamside trees 8 ). This indicates that refinements to the IM technique are needed before IM-CRDS can be useful in natural abundance studies.…”
mentioning
confidence: 91%